Efficacy, immunogenicity, and safety of a plant-derived, quadrivalent, virus-like particle influenza vaccine in adults (18–64 years) and older adults (≥65 years): two multicentre, randomised phase 3 trials. Issue 10261 (7th November 2020) - Ward, Brian J; Makarkov, Alexander; Séguin, Annie; Pillet, Stéphane; Trépanier, Sonia; Dhaliwall, Jiwanjeet; Libman, Michael D; Vesikari, Timo; Landry, Nathalie
Summary: Background: Seasonal influenza remains a substantial public health threat despite the availability of egg-derived and other vaccines. Plant-based manufacturing might address some of the limitations of current vaccines. We describe two phase 3 efficacy studies of a recombinant quadrivalent virus-like particle (QVLP) influenza vaccine manufactured in plants, one in adults aged 18–64 years (the 18–64 study) and one in older people aged 65 years and older (the 65-plus study). Methods: We did two randomised, observer-blind, multinational studies in the northern hemisphere in the 2017–18 (the 18–64 study) and 2018–19 (the 65-plus study) influenza seasons. The 18–64 study was done at 73 sites and the 65-plus study was done at 104 sites, both across Asia, Europe, and North America. In the 18–64 study, inclusion criteria were body-mass index less than 40 kg/m 2 ; age 18–64 years at screening visit; and good health. In the 65-plus study, inclusion criteria were body-mass index of maximum 35 kg/m 2 ; aged 65 years or older at screening visit; not living in a rehabilitation centre or care home; and no acute or evolving medical problems. Participants in the 18–64 study were randomly assigned (1:1) to receive either QVLP vaccine (30 μg haemagglutinin per strain) or placebo. Participants in the 65-plus study were randomly assigned (1:1) to receive QVLP vaccine (30 μg haemagglutinin per strain) or quadrivalent inactivated vaccine (QIV; 15 μg haemagglutinin per strain). The primary outcome in the 18–64 study was absolute vaccine efficacy to prevent laboratory-confirmed, respiratory illness caused by antigenically matched influenza strains. The primary outcome in the 65-plus study was relative vaccine efficacy to prevent laboratory-confirmed influenza-like illness caused by any influenza strain. The primary analyses were done in the per-protocol population and safety was assessed in all participants who received the assigned treatment. These studies are registered with ClinicalTrials.gov (18–64 study NCT03301051 ; 65-plus study NCT03739112 ). Findings: In the 18–64 study, between Aug 30, 2017, and Jan 15, 2018, 10 160 participants were randomly assigned to receive either QVLP vaccine (5077 participants) or placebo (5083 participants). The per-protocol population consisted of 4814 participants in the QVLP group and 4812 in the placebo group. The study did not meet its primary endpoint of 70% absolute vaccine efficacy for the QVLP vaccine (35·1% [95% CI 17·9 to 48·7]) against respiratory illness caused by matched strains. 55 (1·1%) of 5064 participants in the QVLP group versus 51 (1·0%) of 5072 in the placebo group had a serious adverse event. Four (0·1%) and six [0·1%] participants had severe treatment-related treatment-emergent adverse events. In the 65-plus study, between Sept 18, 2018, and Feb 22, 2019, 12 794 participants were randomly assigned to receive either QVLP vaccine (6396 participants) or QIV (6398 participants). The per-protocol population consisted of 5996 participants in the QVLP group and 6026 in the QIV group. The study met its primary non-inferiority endpoint with a relative vaccine efficacy of the QVLP vaccine for the prevention of influenza-like illness caused by any strain of 8·8% (−16·7 to 28·7). 263 (4·1%) of 6352 participants in the QVLP group versus 266 (4·2%) of 6366 in the QIV group had serious adverse events (one [<0·1%] vs two [<0·1%] were considered treatment-related); one (<0·1%) versus three (<0·1%) participants had severe treatment-related treatment-emergent adverse events. Interpretation: These efficacy studies are the first large-scale studies of any plant-derived human vaccine. Together, they show that the plant-derived QVLP vaccine can provide substantial protection against respiratory illness and influenza-like illness caused by influenza viruses in adults. QVLP vaccine was well tolerated and no major safety signal arose in participants who received QVLP vaccine across the two studies. Funding: Medicago.